2020
DOI: 10.3390/v12090948
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prevalence of Phascolarctid Gammaherpesvirus Types 1 and 2 in South Australian Koala Populations

Abstract: To determine Phascolarctid gammaherpesviruses (PhaHV) infection in South Australian koala populations, 80 oropharyngeal swabs from wild-caught and 87 oropharyngeal spleen samples and swabs from euthanased koalas were tested using two specific PCR assays developed to detect PhaHV-1 and PhaHV-2. In wild-caught koalas, active shedding of PhaHV was determined by positive oropharyngeal samples in 72.5% (58/80) of animals, of which 44.8% (26/58) had PhaHV-1, 20.7% (12/58) PhaHV-2 and 34.5% (20/58) both viral subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…[35][36][37] A recent molecular and serological study of wild koala populations in South Australia showed both PhaHV-1 and PhaHV-2 were highly prevalent, with over 66% of koalas actively shedding the virus, but the koalas studied showed no clinical signs of disease. 47 To our knowledge, this is the first alphaherpesvirus reported in a koala, associated with severe respiratory disease.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…[35][36][37] A recent molecular and serological study of wild koala populations in South Australia showed both PhaHV-1 and PhaHV-2 were highly prevalent, with over 66% of koalas actively shedding the virus, but the koalas studied showed no clinical signs of disease. 47 To our knowledge, this is the first alphaherpesvirus reported in a koala, associated with severe respiratory disease.…”
Section: Discussionmentioning
confidence: 84%
“…Herpesviruses previously isolated from koalas include two gammaherpesviruses; Phascolarctid gammaherpesvirus 1 (PhaHV‐1) and Phascolarctid gammaherpesvirus 2 (PhaHV‐2) 35–37 . A recent molecular and serological study of wild koala populations in South Australia showed both PhaHV‐1 and PhaHV‐2 were highly prevalent, with over 66% of koalas actively shedding the virus, but the koalas studied showed no clinical signs of disease 47 . To our knowledge, this is the first alphaherpesvirus reported in a koala, associated with severe respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koala retrovirus (KoRV) is another pathogen infecting koalas that has been associated with chlamydial infections and neoplasia [ 6 , 7 ]. Two recently discovered gammaherpesviruses, phascolarctid gammaherpesvirus 1 (PhaHV-1) [ 8 ] and phascolarctid gammaherpesvirus 2 (PhaHV-2) [ 9 ], infect koalas, with research on distribution and prevalence currently limited to South Australian and Victorian koala populations [ 10 , 11 ]. Gammaherpesviruses are one of three subfamilies of double-stranded DNA viruses, Herpesviridae , along with the Alpha - and Betaherpesvirinae .…”
Section: Introductionmentioning
confidence: 99%
“…These interactions suggest that immune status and co-infections may be playing a role in disease progression in koalas. For precautionary risk management in koala rehabilitation facilities, PhaHV-1 is considered of higher priority due to its association with KoRV, and its association with older koalas suggesting it is horizontally transmitted, while PhaHV-2 may be acquired early in life through mother to offspring transmission [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%